Microfluidics-based encapsulation of isoniazid in egg white/carrageenan microparticles for sustained release - Robinson C. Marengo (Elsevier, 2021)
The prevalence of tuberculosis continuously grows and there is an imperious need to improve the therapeutic efficacy of approved drugs for clinical use. Here we report the encapsulation of isoniazid (INH) in egg white/κ-carrageenan microparticles, which are intended for drug vehiculation through the gastrointestinal tract and controlled release in the ileum. Spherical and highly monodisperse microparticles (255 mm average diameter) were obtained by droplet-based microfluidics and subsequent microwave irradiation. The entire amount of INH added to the particles was encapsulated. Infrared spectra revealed the formation of esters, hydrogen bonding, and Maillard reaction in the biopolymer matrix. In vitro release experiments were carried out in media that systematically emulate the stomach and intestinal tract conditions: 37 °C, NaCl 0.05 mol/L, pH 1.6, for the first 2 h, and Tris–HCl 0.1 mol/L, pH 7, for the next 24 h. A small fraction of the loaded INH was released in the first medium and most of the drug was progressively delivered in the second medium. The release profiles of microparticles were analyzed by using classical kinetic models, which enabled to hypothesize the release mechanism of INH from the biopolymer matrix. This knowledge, together with the ability to control the governing parameters of microfluidic elaboration, opens further possibilities for designing optimal prototypes for sustained release.